Influence of process variables on fracture behaviours of AA7075/AA6101 friction stir welded joints. (12th October 2020) - Swaminathan, G.; Kumar, S.D.; Sathiyamurthy, S.; Mathivanan, A.
Friction stir welding (FSW) commonly known as FSW. It is under solid state welding, which is one of the advancement in the field of welding. Even though the technology is not yet fully commercialised yet, there is an increasing trend in the research and analysis on this subject. This paper focuses on the investigation of mechanical properties and fracture behaviours of dissimilar aluminium alloys of AA7075 and AA6101 joints with respect to process control variables. The macro and microstructure, scanning electron microscopy (SEM) were conducted to study domination of process control variables for dissimilar friction stir welded joints. Effective mixing of both the materials joined was obtained at moderate welding speed and tool rotational speed. From this investigation it is found that the joints fabricated with taper cylindrical tool profile provide the better mechanical properties compared to other tool profiles.